The first three Gospels in Greek arranged in parallel columns - Campbell, Colin (Edinburgh, Scotland Oliver and Boyd, 1918)
Includes index.
Donated by Mr John F. Dickson
Keywords: Bible. N.T. Gospels -- harmonies; Bible. N.T. -- Language, style; Greek language